Diabetes, glycated haemoglobin and the risk of myocardial infarction in women and men: a prospective cohort study of the UK Biobank - Woodward, M (American Diabetes Association, 2020)
Objective: Diabetes has shown to be a stronger risk factor for myocardial infarction (MI) in women than men. Whether sex differences exist across the glycaemic spectrum is unknown. We investigated sex differences in the associations of diabetes status and glycated haemoglobin (HbA1c) with the risk of MI.